انتقاء المسؤولية الجنائية للقاذف في النقد الصحفي الهادف - د. مجيد خضر احمد السبعاوي (PROSPECTIVE RESEARCHES, 2023)
Practicing the right of journalitive and aiming critim by the critic under the freedom of opinion of expression and journalism starts from the important, social, cultural and assessing role in frame of democratic diverse conception and within the scope of constitutional lawful legitimacy to do its professional and moral duty in making the public aware facilitating the necessary information and determining the defect and gaps flexibly and transparently for building not destroying aiming at lifting and developing the society which requires belting the lawful and administrative obstacles and obstructions. But the allowed right of literary, are scientific and historical criticism needs some conditions which make the criminal protection of the critic possible even if his criticism is a abusing crime. Some of the conditions are the criticized situation must be fixed and important according to the audience and the criticism must suitable and honest. The critic must have good intention and safe thinking and the criticism must tackle these deeds and actions in reseal and scientific and professional analysis. The criticism must not extend to author's personality and dignity and it is necessary to aim at the public interest, it must also be useful and contribution in modifying the general taste and forming its content and principles. There is no way to talk about the good intention of the abusive critic and even to write or talk publicly. If this criticism is concerned with some peoples life or prevented by the low such the military and secure secrets and inspection secrets and profession secrets.